Students care about stunting in children: Universitas Pendidikan Indonesia community service program in Karawang Village Cianjur Regency - Meizia Ziharani; Salsa Nissa Agustin (Universitas Pendidikan Indonesia, 2024)
Indonesia still faces nutritional problems, which seriously impact the quality of human resources (HR). One of the problems of malnutrition that is still relatively high in Indonesia includes the issue of stunting and emaciation in toddlers, as well as the problem of anemia and chronic energy deficiency (CED) in pregnant women. The theme